Preparation method and application of hydrolyzed nano-enzyme for marine antifouling coating

By preparing hydrolyzed nanoenzymes, the toxicity, insufficient anti-fouling performance and microplastic pollution of the existing marine anti-fouling coating are solved, and a green, environmentally friendly, low-cost and multi-functional marine anti-fouling coating is achieved, with excellent anti-fouling and mechanical properties.

CN119750508APending Publication Date: 2025-04-04QINGDAO UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510063952.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing marine anti-fouling coatings have problems such as accumulation of toxic substances, insufficient anti-fouling performance, and microplastic pollution. The preparation process of nanoenzyme coatings is complex and lacks hydrolytic enzyme activity.

Method used

The preparation method of hydrolyzed nanoenzyme is adopted to prepare manganese selenide nanoenzyme by reacting selenium powder with hydrazine hydrate and manganese salt under specific conditions, and high-performance anti-fouling effect is achieved by blending with the coating.

Benefits of technology

It realizes a green, environmentally friendly, low-cost and multi-functional marine anti-fouling coating, with excellent anti-fouling, anti-corrosion and mechanical properties, and is non-toxic and harmless, and is suitable for all kinds of substrate surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750508A_ABST
    Figure CN119750508A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of antifouling coatings, and particularly relates to a preparation method and application of hydrolyzed nano-enzyme for a marine antifouling coating. The hydrolytic nano-enzyme prepared by the method has phospholipase activity, protease activity, oxide enzyme activity and capability of efficiently removing a biological membrane, can degrade organic phosphorus in the environment, and can be applied to marine antifouling paint; compared with an existing additive with antifouling capability, the additive has the advantages of being antifouling, corrosion-resistant, low in pollution and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antifouling coatings, and specifically relates to a preparation method of a marine antifouling coating using hydrolytic nanoenzymes and an application thereof. Background Art

[0002] Traditional antifouling coatings mainly achieve antifouling effects by releasing toxic substances, such as antifouling agent release coatings such as tributyltin and cuprous oxide, and organic tin self-polishing coatings. However, with the increase in environmental awareness, people have found that toxic fungicides such as tributyltin will accumulate in marine organisms and eventually endanger human health, so they have been banned. The widely used polypropylene-based Wuxi self-polishing coating gives the surface a certain water solubility through the hydrolysis of the side chain, and realizes self-polishing of the surface under the scouring of water flow. However, due to the lack of strong water flow in a static environment, its antifouling performance is not ideal. In addition, the C-C bond in its main chain is difficult to degrade, which easily causes microplastic pollution and brings environmental problems.

[0003] Existing studies have shown that nanozyme coatings can be used for marine antifouling (Patent Publication No.: CN117186770A). However, the nanozymes of these coatings only have oxidative activity, do not have hydrolytic enzyme activity, and the preparation process is complicated. In addition, some nano marine antifouling coatings (such as Patent Publication No.: CN103788812B) contain phenolic resins, which are not friendly to the environment. In order to meet the market demand for green and environmentally friendly marine antifouling technology, it is urgent to develop a multifunctional, environmentally friendly coating that integrates antifouling, anticorrosion, low pollution and low cost. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a marine antifouling coating using hydrolytic nanoenzymes, which is implemented using the following specific scheme:

[0005] Preparation steps

[0006] (1) Selenium powder (0.32 g) was added to a hydrazine hydrate solution (20 ml, 80% concentration), and then heated in an oil bath and stirred for 4 hours to obtain a brown-black solution A;

[0007] (2) dissolving manganese salt (0.05 mmol) in a mixture of deionized water and glycerol (volume ratio 1:4, 25 ml) to obtain solution B;

[0008] (3) Add solution A dropwise to solution B, mix thoroughly at room temperature (20-30°C), transfer to a polytetrafluoroethylene-lined autoclave, and react at 160-200°C for 12 hours. After the reaction is completed, cool to room temperature, filter, and wash with deionized water and anhydrous ethanol three times each to obtain a black precipitate;

[0009] (4) Dry the black precipitate in a vacuum drying oven at 40° C. for 12 hours to obtain the selenide manganese nanozyme.

[0010] Preferred conditions

[0011] (1) In the preparation method, the concentration of selenium powder is preferably 99.9%;

[0012] (2) In the preparation method, the mass of selenium powder is preferably 0.32 g;

[0013] (3) In the preparation method, the concentration of the hydrazine hydrate solution is preferably 80%;

[0014] (4) In the preparation method, the volume of the hydrazine hydrate solution is preferably 20 ml;

[0015] (5) In the preparation method, the amount of manganese salt is preferably 2 mmol / L;

[0016] (6) In the preparation method, the stirring speed is preferably 500 rpm;

[0017] (7) In the preparation method, the temperature of the oil bath is preferably 85°C;

[0018] (8) In the preparation method, the hydrothermal reaction temperature is preferably 180°C.

[0019] The nanozyme preparation process provided by the present invention is simple and efficient, and a high-performance antifouling effect can be achieved by blending with a coating, and the whole process is green and environmentally friendly without any chemical pollution. The prepared coating is non-toxic and harmless, has strong adhesion to the substrate, and can be widely used on the surfaces of various substrates. The coating not only has good mechanical properties, but also exhibits excellent antifouling effects, and has broad application prospects in the fields of biomedicine, marine ships, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 X-ray diffraction pattern of manganese selenide nanozyme

[0021] Figure 2 Effect of coating containing manganese selenide nanozyme

[0022] Figure 3 Fluorescence comparison of the ability of coatings to prevent protein attachment

[0023] Figure 4 Contrast of bacterial colonies on the coating surface

[0024] Figure 5 Comparison of marine antifouling effects DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the present invention, the present invention is now further described in detail in conjunction with specific embodiments. It should also be understood that the following examples are only used for further explanation of the present invention and should not be regarded as limiting the scope of protection of the present invention. Non-essential improvements or adjustments made by those skilled in the art based on the content of the present invention should all be regarded as belonging to the scope of protection of the present invention.

[0026] Example 1: Synthesis of manganese selenide using manganese nitrate as manganese source

[0027] 0.32 g of selenium powder was added to 20 ml of hydrazine hydrate solution, and then stirred in an 85°C oil bath at a stirring rate of 500 rpm for 2 hours to obtain a brown-black solution A. Subsequently, 0.05 mmol of manganese nitrate was dissolved in 25 ml of a solution of deionized water and glycerol in a volume ratio of 1:4 to prepare solution B. Solution A was added dropwise to solution B, and after being fully mixed at room temperature, it was transferred to a high-pressure reactor with a polytetrafluoroethylene lining and reacted at 180°C for 12 hours. After the reaction was completed, the system was cooled to room temperature, the product was collected by suction filtration, and washed with deionized water and anhydrous ethanol 3 times in sequence to obtain a black precipitate. Finally, the black precipitate was placed in a vacuum drying oven and dried at 40°C for 8 hours to prepare the selenide manganese nanozyme, and the selenide manganese nanozyme was subjected to X-ray diffraction analysis. The analysis results are shown in the attached manual. Figure 1 shown.

[0028] Preferred conditions

[0029] (1) In the preparation method, the concentration of selenium powder is preferably 99.9%;

[0030] (2) In the preparation method, the mass of selenium powder is preferably 0.32 g;

[0031] (3) In the preparation method, the concentration of the hydrazine hydrate solution is preferably 80%;

[0032] (4) In the preparation method, the volume of the hydrazine hydrate solution is preferably 20 ml;

[0033] (5) In the preparation method, the amount of manganese salt is preferably 2 mmol / L;

[0034] (6) In the preparation method, the stirring speed is preferably 500 rpm;

[0035] (7) In the preparation method, the temperature of the oil bath is preferably 85°C;

[0036] (8) In the preparation method, the hydrothermal reaction temperature is preferably 180°C.

[0037] Example 2: Synthesis of manganese selenide using manganese acetate as a manganese source

[0038] Add 0.32 g of selenium powder to 20 ml of hydrazine hydrate solution. Then stir in an 85°C oil bath at a stirring rate of 500 rpm for 2 hours to generate a brown-black solution A. Subsequently, 0.05 mmol of manganese acetate was dissolved in 25 ml of a solution of deionized water and glycerol mixed in a volume ratio of 1:4 to prepare solution B. Solution A was added dropwise to solution B, and after being fully mixed at room temperature, it was transferred to a high-pressure reactor with a polytetrafluoroethylene lining and reacted at 180°C for 12 hours. After the reaction was completed, the system was cooled to room temperature, the product was collected by suction filtration, and washed with deionized water and anhydrous ethanol 3 times in sequence to obtain a black precipitate. Finally, the black precipitate was placed in a vacuum drying oven and dried at 40°C for 8 hours to prepare the selenide manganese nanozyme, and the selenide manganese nanozyme was subjected to X-ray diffraction analysis. The analysis results were the same as those in the attached manual. Figure 1 Consistent.

[0039] Preferred conditions

[0040] (1) In the preparation method, the concentration of selenium powder is preferably 99.9%;

[0041] (2) In the preparation method, the mass of selenium powder is preferably 0.32 g;

[0042] (3) In the preparation method, the concentration of the hydrazine hydrate solution is preferably 80%;

[0043] (4) In the preparation method, the volume of the hydrazine hydrate solution is preferably 20 ml;

[0044] (5) In the preparation method, the amount of manganese salt is preferably 2 mmol / L;

[0045] (6) In the preparation method, the stirring speed is preferably 500 rpm;

[0046] (7) In the preparation method, the temperature of the oil bath is preferably 85°C;

[0047] (8) In the preparation method, the hydrothermal reaction temperature is preferably 180°C.

[0048] Example 3: Synthesis of manganese selenide coating

[0049] (1) Slowly add 25 grams of epoxy resin into a reaction vessel containing a mixed solvent of 24 grams of toluene and 16 grams of ethanol. The container should be placed in a well-ventilated environment, and the stirrer should be turned on and stirred at 400 rpm for about 20 minutes until the binder is completely dissolved to form a uniform solution.

[0050] (2) Add 30 g of manganese selenide powder to the above solution, increase the stirring speed to 1000 rpm, and continue stirring for about 40 minutes.

[0051] (3) While maintaining the stirring speed at 1000 rpm, 2 g of a polycarboxylate dispersant was added, and stirring was continued for 10 minutes to allow the dispersant to fully exert its effect and stabilize the dispersion state of the manganese selenide particles.

[0052] (4) Add 3 g of fumed silica thickener and stir at 700 rpm for about 20 minutes to evenly disperse the thickener in the coating and reach a viscosity of 60 Pa·s. During the viscosity adjustment process, a viscometer should be used to monitor the viscosity in real time.

[0053] (5) Filter the coating with a 300-400 mesh filter to remove large particles and impurities that are not well dispersed, and finally prepare a marine anti-fouling manganese selenide coating, and apply the obtained manganese selenide coating to the surface of AH32 steel plate to form a coating. The coating effect is as shown in the attached manual. Figure 2 shown.

[0054] Preferred conditions

[0055] (1) In the method for preparing the manganese selenide coating, the mass of the fumed silica is 3 grams;

[0056] (2) In the method for preparing the manganese selenide coating, the purity of the fumed silica is 99.9%;

[0057] (3) In the method for preparing the manganese selenide coating, the mass of the polycarboxylate dispersant is 2 g;

[0058] (4) In the method for preparing the manganese selenide coating, the dispersion time of the coating disperser is 70 minutes;

[0059] (5) In the method for preparing the manganese selenide coating, the particle size of the particles ground is less than 50 microns;

[0060] (6) In the method for preparing the manganese selenide coating, the masses of the epoxy resin, manganese selenide, toluene, and ethanol are 25 g, 30 g, 24 g, and 16 g, respectively;

[0061] (7) In the method for preparing the manganese selenide coating, the viscosity of the coating is adjusted to 60 Pa·s.

[0062] Comparative Example

[0063] Comparative Example 1: This comparative example provides a method for preparing an epoxy zinc-rich primer coating

[0064] (1) Place 1.5 g of epoxy resin in a glass beaker. Stir at 300-500 rpm using a small magnetic stirrer. Slowly add 0.4 g of butanol and continue stirring for 15 minutes until the epoxy resin is fully dissolved.

[0065] (2) Add 0.08 g of dispersant and 0.07 g of anti-settling agent to the dissolved epoxy resin solution. Continue stirring at a speed of about 300-500 rpm for 10 minutes to evenly disperse the additives in the solution.

[0066] (3) Gradually add 8 grams of zinc powder to the epoxy resin solution containing additives, stirring while adding, and pay attention to the slow stirring speed. After all the addition, increase the stirring speed to 1000-1500 rpm, stir for about 30-60 minutes, try to make the zinc powder fully and evenly dispersed in the resin solution, and filter the coating with a 100-200 mesh filter.

[0067] (4) Use a special cleaning agent to remove the oil, grease and dirt on the surface of the AH32 steel plate. Use a good quality brush to evenly apply the primer on the surface of the steel plate. When brushing, pay attention to keep the brush at an angle of 45-60 degrees to the surface of the steel plate, and apply in a certain order (such as from top to bottom, from left to right) to avoid missing or dripping. The thickness of each brushing should not be too thick, and the general dry film thickness is controlled at about 20-30 microns.

[0068] (5) Allow the primer to dry naturally in a well-ventilated environment. The ambient temperature should be between 5-35°C and the relative humidity should not exceed 85%. The natural drying time is generally 24-48 hours, depending on the environmental conditions and the thickness of the primer.

[0069] The same steel plate as that in Comparative Example 1 was used for testing.

[0070] Effect test of the above coating:

[0071] The antifouling coatings obtained in Example 3, Comparative Example 1 and Comparative Example 2 were subjected to a protein anti-adhesion performance test, an antibacterial performance test and a marine antifouling effect test to comprehensively evaluate the antifouling effect of the antifouling coatings prepared by the present invention.

[0072] (1) Protein anti-attachment performance test: In the process of marine fouling organisms attaching, protein is the first substance to contact the surface of the substrate, and its aggregation lays the foundation for the formation of biofilm. Therefore, in order to fundamentally prevent the attachment of fouling organisms, it is first necessary to evaluate the anti-attachment performance of the anti-fouling coating against protein.

[0073] The present invention uses bovine serum albumin labeled with fluorescein isothiocyanate to test the surface of the antifouling coating, and observes the adsorption behavior of the protein on the coating surface through a fluorescence microscope to evaluate the anti-protein adhesion ability of the coating. The specific test steps are as follows:

[0074] In a dim light environment, use a pipette to measure 50 μl of fluorescein isothiocyanate-labeled bovine serum albumin solution, drop it evenly on the coating surface, and cover it with a coverslip to spread the solution evenly. After standing for 24 hours, remove the coverslip and wash the coating surface with phosphate buffer.

[0075] The coating surface was photographed and observed using a fluorescence microscope. The parameters of the fluorescence microscope were set to: excitation light wavelength 488 nanometers, emission light wavelength range 500-550 nanometers. The test results are shown in the attached manual. Figure 3 As shown in the instruction manual, Figure 3 (a) to (c) correspond to the protein adsorption on the coating surface of Example 3, Comparative Example 1 and Comparative Example 2, respectively.

[0076] By comparing the instructions attached Figure 3 The test results show that Example 3 (attached to the specification) Figure 3 The amount of protein adsorbed on the coating surface of (a)) is the lowest, which is significantly better than that of Comparative Example 1 (attached to the specification) Figure 3 (b)) and Comparative Example 2 (attached to the specification Figure 3 (c)). This shows that the antifouling coating prepared by the present invention has excellent protein anti-adhesion ability and good antifouling effect.

[0077] (2) Antibacterial performance test: The key step for marine fouling organisms to attach to the hull surface is that bacteria attach to the substrate surface by secreting sticky polysaccharides and forming a biofilm, and the formation of the biofilm provides a basis for the subsequent attachment of marine fouling organisms. Therefore, the key to anti-fouling coatings lies in effectively inhibiting the biofilm formation ability of marine bacteria.

[0078] In order to verify the antibacterial and sterilization performance of the antifouling coating provided by the present invention to prevent the formation of biofilm, this study selected common marine Gram-positive Bacillus and Gram-negative Pseudomonas to test the antibacterial ability of the coating prepared in Example 3 and Comparative Examples 1 and 2. The specific test steps are as follows:

[0079] Select bacteria and inoculate them in LB liquid culture medium, shake and mix them at 220 rpm in a 37°C constant temperature shaker, and culture them until the exponential growth phase. Soak the substrate sample with the coating in LB liquid culture medium, shake and mix it at 220 rpm in a 37°C constant temperature shaker. After 6 hours of culture, remove the substrate sample from the LB liquid culture medium, shake and elute the bacteria attached to the coating surface with an appropriate amount of phosphate buffer to obtain a bacterial solution. Take 0.5 ml of the bacterial solution and dilute it for counting on the coating plate, and take pictures of the colony formation on the surface of the antifouling coating (as shown in the attached manual). Figure 4 shown).

[0080] Attached to the instruction manual Figure 4The comparison results of (a) to (c) show that the surface of the coating prepared in Example 3 (see Appendix Figure 4 The number of colonies in (a)) was significantly lower than that in Comparative Example 1 (attached to the specification). Figure 4 (b)) and Comparative Example 2 (attached to the specification Figure 4 (c)), indicating that the antifouling coating prepared by the present invention has excellent antibacterial properties.

[0081] (3) Marine antifouling effect test: In order to more comprehensively evaluate the antifouling performance of the antifouling coating prepared by the present invention in practical applications, the present invention conducted a marine antifouling effect test on the antifouling coating prepared in Example 3 and Comparative Examples 1 and 2, and observed the attachment of fouling organisms to the surface of the antifouling coating in a real marine environment.

[0082] The marine antifouling effect test was conducted on a floating raft in the Yellow Sea area of ​​Qingdao. The steel plate samples coated with the antifouling coating were sampled and photographed on the 15th, 30th, 60th and 90th days to monitor the attachment of fouling organisms on the coating surface. The actual pictures of the samples of Example 3 and Comparative Examples 1 and 2 are as attached to the specification. Figure 5 shown.

[0083] On the 15th day, the instructions Figure 5 The results show that the surface of the steel plate sample of Example 3 has almost no change, and no bacteria and organic molecules are found attached to the surface after detection and analysis. The surfaces of the steel plate samples of Comparative Examples 1 and 2 have slight changes, with a small amount of bacteria and organic molecules attached, of which the amount of attachment in Comparative Example 1 is slightly higher than that in Comparative Example 2, but no obvious biofilm is formed in either of them.

[0084] On the 30th day, the instructions Figure 5 The results show that there is still no significant change on the surface of the steel plate sample of Example 3. After testing, only a very small amount of bacteria and organic molecules are found to be attached. The bacteria and organic molecules attached to the surface of the steel plate samples of Comparative Examples 1 and 2 increase, and preliminary biofilms have formed in some areas.

[0085] On the 60th day, the instructions Figure 5 It shows that only a small amount of bacteria and organic molecules are attached to the surface of the steel plate sample of Example 3, and no obvious biofilm is formed. A relatively complete biofilm is formed on the surface of the steel plate samples of Comparative Examples 1 and 2, and bacteria and microbial communities gather.

[0086] On the 90th day, the instructions Figure 5 It shows that a small amount of biofilm begins to form on the surface of the steel plate sample of Example 3, but the overall attachment is relatively light. The biofilm attached to the surface of the steel plate samples of Comparative Examples 1 and 2 further thickens, and the degree of contamination is significantly aggravated.

[0087] The comprehensive experimental results show that the antifouling coating prepared in Example 3 exhibits excellent antifouling performance in the actual marine environment and has a significant inhibitory effect on the attachment of bacteria and organic molecules, while the antifouling effects of Comparative Examples 1 and 2 decrease successively.

[0088] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a marine antifouling coating using hydrolytic nanoenzymes and its application, characterized in that The method comprises the following steps: (1) adding selenium powder (0.32 g, purity 99.9%) to a hydrazine hydrate solution (20-40 ml, concentration 80%), and then stirring in an oil bath at 85-90° C. at a stirring rate of 500-700 rpm for 2-4 hours to obtain a brown-black solution A; (2) adding manganese salt (0.05 mmol) to a mixture of deionized water and glycerol (volume ratio 1:4, 25 ml) to obtain solution B; (3) Then, solution A was added dropwise to solution B, mixed evenly at room temperature (20-30°C), and transferred to a high-pressure reactor with a polytetrafluoroethylene liner and treated at 180°C for 12 hours. After the reaction was completed, it was cooled to room temperature (20-30°C), filtered, and washed three times with deionized water and anhydrous ethanol in sequence to obtain a black precipitate; (4) Dry (3) in a vacuum drying oven at 40-60° C. for 8-12 hours to obtain manganese selenide nanozyme.

2. The manganese selenide nanozyme obtained by the preparation method according to claim 1, characterized in that It has phosphatase activity, protease activity, oxidase activity and the ability to remove biofilm, and its biofilm removal efficiency is ≥98%.

3. The manganese salt as claimed in claim 1 can be selected from any one of manganese nitrate, manganese carbonate, manganese acetate or other equivalent manganese sources.

4. The nanozyme as described in claim 1 can be used in ship antifouling paint, marine antifouling paint and other heavy anti-corrosion paints.

5. The nanozyme as described in claim 1 can be used to degrade organic pollutants, wherein the efficiency of degrading organophosphorus pesticides reaches ≥95%.

Citation Information

Patent Citations

  • A nano marine antifouling coating

    CN103788812B

  • Antifouling coating of nano-enzyme synergistic biomass material as well as preparation method and application of antifouling coating

    CN117186770A